Vitamin A Deficiency during the Perinatal Period and First Weeks of Life Modifies Vitamin A and Lipid Postprandial Metabolism in Both Female and Male Young Rats. Issue 21 (27th September 2021) - Antoine, Tiffany; Borel, Patrick; Govers, Roland; Meiller, Laure; Guichard, Philippe; Halimi, Charlotte; Gonzalez, Teresa; Nowicki, Marion; Sauvinet, Valérie; Grino, Michel; Reboul, Emmanuelle
Abstract : Scope: The effect of vitamin A deficiency on vitamin A and lipid postprandial metabolism in young rats is addressed, considering the effect of sex. Methods and Results: Sprague‐Dawley rats are fed either 400 UI.kg −1 vitamin A diet (vitamin A‐deficient (VAD) diet) or 2300 UI.kg −1 vitamin A (control diet), before being mated. Mothers receive the same VAD or control diet during gestation and lactation. Offspring receive the same diet than mothers until 8 weeks of age. VAD diet‐fed female and male offspring display a severe vitamin A deficiency with no body weight or glucose tolerance defects. Fasting plasma triglyceride concentrations are decreased in VAD diet‐fed animals compared to controls ( p < 0.05). Retinyl ester postprandial responses after vitamin A gavage, expressed as area under the curves, are not different in VAD diet‐fed and control animals, although retinyl ester postprandial peak is significantly delayed ( p < 0.05) in VAD diet‐fed rats. Lipids also accumulate in the distal part of the intestine after gavage and [1‐ 13 C]‐oleate postprandial response is decreased in VAD diet‐fed males. Conclusion: Vitamin A deficiency modulates both vitamin A absorption rate and lipid postprandial metabolism, which can partly explain the altered fasting lipid status observed in VAD diet‐fed offspring. Abstract : Rats are fed either 400 UI kg −1 vitamin A diet (vitamin A deficient (VAD)) or 2300 UI kg −1 vitamin A (control diet), before being mated. Offspring receive the same diet than mothers until week 8. Compared to control offspring, VAD offspring presents decreased plasma triglycerides at fast, a delayed retinyl ester postprandial response, and a decreased oleate postprandial response after gavage. Vitamin A perinatal deficiency thus induces modulations in vitamin A and lipid postprandial metabolism.